New Frontiers in Prostate Cancer Treatment: Are We Ready for Drug Combinations with Novel Agents? - Gaetano Aurilio; Alessia Cimadamore; Matteo Santoni; Franco Nolè; Marina Scarpelli; Francesco Massari; Antonio Lopez-Beltran; Liang Cheng; Rodolfo Montironi (Cells, 2020)
Medical treatment for metastatic castration-resistant prostate cancer (mCRPC) patients has progressively been evolving from a nonspecific clinical approach to genomics-oriented therapies. The scientific community is in fact increasingly focusing on developing DNA damage repair (DDR) defect-driven novel molecules, both as single-agent therapy and in combined treatment strategies. Accordingly, research is under way into combined drug therapies targeting different pathways, e.g. androgen receptor signaling (ARS) and poly (adenosine diphosphate [ADP]-ribose) polymerase (PARP) enzymes, immune checkpoint (IC) and PARP, IC, and ARS, and prostate-specific membrane antigen (PSMA). In an attempt to formulate evolving treatment paradigms in mCRPC patients, here we selected clinical research into patients undergoing therapies with emerging molecules, with particular emphasis towards PARP-, IC-, and PSMA-inhibitors. In order to focus on those molecules and drug combinations most likely to be translated into routine clinical care in the near future, we selected only those clinical studies currently recruiting patients. A PubMed search focusing on the keywords “prostate cancer”, “metastatic castration-resistant prostate cancer”, “DDR pathways”, “ARS inhibitors”, “PARP inhibitors”, “IC inhibitors”, “PSMA-targeting agents”, and “drug combinations” was performed.